Application of Lean Management to Improve Operational Efficiency in Green Tourism: An Analytic Hierarchy Process (AHP) Approach - Hernum Daya Wati; Abi Hanif Dzulquarnain (Universitas Negeri Semarang, 2026)
This study aims to examine the application of Lean Management in improving operational efficiency in the Green Tourism sector by using the Analytic Hierarchy Process (AHP) approach as a decision-making tool. Green tourism requires efficient, sustainable, and environmentally friendly operational management, but in practice there are still often wasted resources, processes that do not add value, and less structured decision-making. The Lean Management approach is used to identify and eliminate waste activities in the tourism operational process, such as excessive energy use, inefficient service flows, and suboptimal facility management. Meanwhile, the AHP method is applied to determine the most effective Lean strategy priorities by considering various criteria, including cost efficiency, environmental impact, service quality, and tourist satisfaction. This study uses a quantitative method by collecting data through questionnaires and interviews with green tourism destination managers. The results of the AHP analysis are expected to be able to produce priority weight on alternative Lean Management implementations that are most in line with the characteristics of green tourism. The findings of this study are expected to be strategic recommendations for tourism managers in improving operational efficiency while maintaining the principles of environmental sustainability.